Innovative Waste Management Solutions for Building Sustainable Cities and Enhancing Community Resilience - Sarita Meena; Sharwan Kumar Bishnoi (International Journal of Environmental Planning and Development Architecture, 2025)
The swift growth of urban areas presents considerable difficulties in waste management, as conventional disposal techniques lead to environmental harm. This study explores innovative green technologies designed to transform urban waste into valuable biomaterials and biofuels, fostering a circular economy and environmental conservation. The focus is on real-time monitoring systems, RFID-enabled waste tracking, and IoT-based platforms, which optimize waste collection and segregation, enabling efficient recovery of materials for biofuel production. Case studies from cities like San Francisco, Tokyo, and Bengaluru highlight how these technologies reduce landfill waste and promote the production of biofuels and organic fertilizers. Real-time monitoring provides actionable data for waste management, improving efficiency. RFID systems encourage responsible disposal by tracking individual contributions, while IoT-based platforms integrate these technologies, offering a comprehensive solution for managing waste across urban areas. The research underscores the critical role of community participation, policy support, and public-private partnerships in scaling these innovations. By incorporating waste-to-biomaterial and biofuel technologies, cities can greatly lower their carbon emissions and play a key role in environmental conservation. This study provides practical insights for urban planners, policymakers, and environmental stakeholders looking to implement sustainable waste management solutions aligned with circular economy principles.
Keywords: Biofuels; Biomaterials; Environmental Conservation; Waste management; circular economy; green technology; sustainable development goals (SDGs); zero waste cities